Integrated geochemical, mineralogical, and microstructural identification of faults in tunnels and its application to TBM jamming analysis. (October 2022) - Xu, Z.H.; Yu, T.F.; Lin, P.; Wang, W.Y.; Shao, R.Q.
Highlights: An integrated fault identification method was proposed. The FT1 fault of the Yellow Diversion 2 bid section was successfully identified. The mechanical properties of the fault rock were significantly weakened. The engineering geological causes of the jamming accident were analyzed. Chemical grouting backfilling and grouting reinforcement measures were implemented. Abstract: Faults are frequently one of those adverse geological conditions that jam tunnel boring machines (TBMs). However, the identification of faults and the engineering geological analysis of the corresponding jamming accidents still lack a better understanding. In this study, a method for fault identification through integration of the microstructural, geochemical, and mineralogical characteristics of the rocks was developed. The method was applied to the TBM 2 bid section of the Central Shanxi Yellow River Diversion Project to determine the geological characteristics of the rocks using optical thin section, X-ray fluorescence, and X-ray diffraction analysis. The results of this study provide evidence for the establishment of fault-induced geochemical effects and mineral transformations. Not only were fault FT1 and the nearby fault rock successfully identified, but evidence of weakened mechanical properties of the fault rocks was also obtained. The structure and composition of the migmatitic granites were strongly altered by long-term tectonic stress fracturing and pervasive acidic fluid leaching, forming loosely fractured, poorly integrated granitic granulate-porphyroclastic rock. The fault rock is rich in clay minerals and solid graphite lubricant. The comprehensive effect of the fault rock's characteristics, geological structure, groundwater, and ground stress led to the collapse of the weak rock within the fault zone, which was the main geological reason for the jamming accident. Finally, we proposed corresponding engineering treatment measures and subsequent excavation recommendations. The proposed method can be used for the integrated identification of faults in underground engineering and mining projects, and the geological analysis of TBM jamming accidents.